Electrical transport in C-doped GaAs nanowires: Aurface effects - Casadei, Alberto; Schwender, Jil; Russo-Averchi, Eleonora; Rueffer, Daniel; Heiss, Martin; Alarco-Llado, Esther; Jabeen, Fauzia; Ramezani, Mohammad; Nielsch, Kornelius; Fontcuberta I Morral, Anna (Physica Status Solidi-Rapid Research Letters, 2013)
The resistivity and mobility of carbon-doped GaAs nanowires have been studied for different doping concentrations. Surface effects have been evaluated by comparing unpassivated with passivated nanowires. We directly see the influence of the surface: the pinning of the Fermi level and the consequent existence of a depletion region lead to an increase of the mobility up to 30 cm2/Vs for doping concentrations lower than 3 × 1018 cm-3. Electron beam induced current measurements show that the minority carrier diffusion path can be as high as 190 nm for passivated nanowires. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Carrier mobility; Doping; GaAs; III-V semiconductors; Nanowires; Surface passivation